Experiencing Grounded Theory - Kari Allen-Hammer; Lisa Goldberg; Elizabeth Kellogg; Kelisa Underwood; Kara L. Vander Linden (Grounded Theory Review: An International Journal)
Experiencing Grounded Theory takes the reader on an enjoyable, easy-to-read journey through Simmons’s 55 years of learning, doing, mentoring, teaching, and applying grounded theory. It is an engaging book written for beginner to experienced grounded theorists. It is laid out in a well-organized fashion, beginning with Simmons’s introduction to grounded theory and progressing through his years of teaching the methodology. This article provides a quick overview of each chapter. While there are many books written on grounded theory, few explain the method as clearly as this one. It is a recommended read for both novice and practicing grounded theorists.